Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen dengan Ketepatan Waktu Pengiriman sebagai Variabel Moderasi pada PT JNE Express Cabang Karangawen - Nurul Dyah Ayu Fajrin; Firdaus Firdaus; Muhammad Syaiful Huda; Dien Maulana Akbar; Jumai Jumai; Fitri Amalia Pratama; Sherly Vera Ari Sabrina (Jurnal Manajemen Bisnis Era Digital, 2024)
This research is a type of quantitative research with accidental sampling method. The population in this study were 100 consumers who used the services of JNE Express Karangawen branch with a total sample of 100 people. The data collection technique uses a questionnaire that has been tested for the validity and reliability of the data. The data analysis method used consisted of normality test, multicollinearity test, and heteroscedasticity test. While the data analysis techniques used to answer the hypothesis include moderated regression analysis (MRA), t test, F test, and analysis of the coefficient of determination (R2). The results of this study indicate that (1) service quality has a positive and significant effect on customer satisfaction with a regression coefficient of service quality of 0.374 and a value of tcount > ttable that is 3.578 > 1.984 and a significance value of 0.000 <0.05. (2) timeliness of delivery is a moderating variable that strengthens the effect of service quality on delivery time satisfaction with a value of tcount > ttable which is 3,559 > 1,984 and a significance value of 0,003 < 0,05. (3) service quality has a positive and significant effect on customer satisfaction with timeliness of delivery as a moderating variable with a regression coefficient value of 0.18 on time delivery and a value of Fcount > Ftable that is 4.845 > 3.937 and a significance value of 0.042 < 0.05.